Hysterical men : war, psychiatry, and the politics of trauma in Germany ; 1890 - 1930 - Lerner, Paul Frederick (Cornell studies in the history of psychiatry, 2003)
"Paul Lerner traces the intertwined histories of trauma and male hysteria in German society and psychiatry and shows how these concepts were swept up into debates about Germany's national health, economic productivity, and military strength in the years surrounding World War I. From a growing concern with industrial accidents in the 1880s through the shell shock "epidemic" of the war, male hysteria seemed to bespeak the failings of German masculinity. In response, psychiatrists struggled to turn male hysterical bodies into fit workers and loyal political subjects." "Hysterical Men shows how wartime psychiatry furthered the process of medical rationalization. Lerner views this not as a precursor to the brutalities of Nazi-era psychiatry, but rather as characteristic of a more general medicalized modernity. The author asserts, however, that psychiatry's continual scepticism toward trauma resonated powerfully with the radical right's celebration of war and violence and its supposedly salutary effects on men and nations."--BOOK JACKET.